A Metal–Organic Supramolecular Box as a Universal Reservoir of UV, WL, and NIR Light for Long‐Persistent Luminescence. (4th February 2019) - Wang, Zheng; Zhu, Cheng‐Yi; Yin, Shao‐Yun; Wei, Zhang‐Wen; Zhang, Jian‐Hua; Fan, Ya‐Nan; Jiang, Ji‐Jun; Pan, Mei; Su, Cheng‐Yong
Abstract: Long persistent luminescence (LPL) materials have a unique photophysical mechanism to store light radiation energy for subsequent release. However, in comparison to the common UV source, white‐light (WL) and near‐infrared (NIR) excited LPL is scarce. Herein we report a metal–organic supramolecular box based on a D–π–A‐type ligand. Owing to the integrated one‐photon absorption (OPA) and two‐photon absorption (TPA) attributes of the ligand, the heavy‐atom effect of the metal center, as well as π‐stacking and J‐aggregation states in the supramolecular assembly, LPL can be triggered by all wavebands from the UV to the NIR region. This novel designed supramolecular kit to afford LPL by both OPA and TPA pathways provides potential applications in anti‐counterfeiting, camouflaging, decorating, and displaying, among others.